THE EFFECT OF INDIGENOUS REJECTION ON THE ACCEPTANCE OF THE CONCEPT OF NATION BY ETHNIC CHINESE IN THE SHORT STORY "CLARA ATAWA, A RAPE WOMAN" - Hiasa, Fina (EUFONI: Journal of Language, Literary, and Cultural Studies, 2021)
Upstone (2009) in his book Spatial Politics in the Postcolonial Novel in the section Shifting Scale proposes alternatives to free themselves from the colonial construction that has taken root, namely the concept of langer than nation and smaller than nation. The nation is the result of the struggle to continue colonial construction so that the two alternative goals of self-liberation from colonial construction are the same, namely to dissolve national boundaries which are the result of the construction of colonialism. This paper will discuss the short story "Clara Atawa Wanita Yang Diperkosa" by Seno Gumira Ajidarma in the context of post-space and its relationship with the nation. The author will describe the effect that occurs from the unification of local spaces into a nation that occurs in this short story. Furthermore, the author will describe the alternative solutions to the concept of nation which is a colonial construction. The conclusion of the short story "Clara Atawa Wanita Yang Diperkosa" is that the continuation of nation and nationalism which is a colonial construction shows its negativity, namely violations of human rights (murder, rape, and looting of ethnic Chinese), so in other words the smaller scale in the end always submits. in the nation which is a colonial construction. So that the best alternative in the context of this short story is to use the concept of smaller than nation in which Clara's character returns to the particular space or local space. Keywords: Clara Atawa, Nation Concept, Postcolonialism, Upstone